CFD based Improvement of Thai Irrigation Pump - Wasinarom, Kittipass; Boonchauy, Dachdanai; Charoensuk, Jarruwat (My University, 2020)
Evaluation phase which was partial fulfilment of the beginning phase of "Development of Performance test rig and Efficiency improvement of impeller in Thai irrigation pump project" is presented in this paper. Overall flow field in the pump system that consisted of inlet, impeller and stator vane of the available pump was analyzed using commercial Computational Fluid Dynamics (CFD) code. The goal of this investigation is to obtain more understanding of energy dissipation which results from shear stress that developed within the flow field in each section of the pump. The improvement measure is then conducted with the concern of manufacturing difficulties. High dissipation flow structure was observed around the impeller outlet. Jet-wake and recirculation flow were observed. The first improvement measure was conducted by adding the bluff body in the flow channel to alleviate jet-wake structure and delay flow separation. After the implementation of the optimized bluff body around the impeller exit, CFD results indicated around 3-8% improvement compared with the CFD results of the available pump for the entire range of operating conditions.
Keywords: CFD; Improvement; Pump; Turbo-machine